If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 25 + -1x Reorder the terms: 7 + 5x = 25 + -1x Solving 7 + 5x = 25 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7 + 5x + x = 25 + -1x + x Combine like terms: 5x + x = 6x 7 + 6x = 25 + -1x + x Combine like terms: -1x + x = 0 7 + 6x = 25 + 0 7 + 6x = 25 Add '-7' to each side of the equation. 7 + -7 + 6x = 25 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 25 + -7 6x = 25 + -7 Combine like terms: 25 + -7 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| 9x-10=34-2x | | 2xX+-.5=-.75 | | -12x+5=17 | | 7a+21b=36 | | 2y+10x-4=0 | | 2xX+.5=.75 | | 25c^2+80c+64= | | 7a+21b= | | 4(-5x-5)=120 | | 2xT+-.5=-.75 | | 25m^2+4n^2-4n-1= | | x^3-12x^2+36x-32=0 | | 9x(x+8)=4x+32 | | -8-4x=3-7x | | -8.4x=58.8 | | 7a+3=14 | | 2lx+2l=18 | | 5(7-2m)+5=90 | | 2x^2-8x+15=11 | | 45-x=7 | | -7(2b+1)+(15b-3)=0 | | (-5u^3v^4+9u)+(-5u^3v^4-8u+8u^2v^2)+(-8u^4v^2+8u^3v^4)= | | 1.4q-1.3-1.8q=-1.4q-2.8 | | 4x+23=12x-73 | | 3x+4=59 | | 12-3=10x+3 | | y+34=18 | | 7+2x^2+4x^2=37 | | 5(5x+13)=25 | | 9m+3(m+12)-2= | | 0.45x+.05(2-x)=.10(-55) | | 4x(1-3x)=0 |